2020
DOI: 10.1097/gox.0000000000002806
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Thromboprophylaxis in Digital Replantation: A Systematic Review

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…Thus, low-quality evidence shows that a therapeutic dose of intravenous unfractionated heparin leads to a higher risk of complications when compared with heparin given as an intermittent bolus of unfractionated heparin or subcutaneous heparin, or prostaglandin E1 or no heparin. These results differ from two recent systematic reviews (including one with meta-analysis) that did not find clear evidence of higher complications associated with perioperative thromboprophylaxis in digital replantation (Lin et al, 2020;Reissis et al, 2020).The meta-analysis compared unfractionated heparin use with low-molecular weight heparin and found no clear evidence of higher complications associated with unfractionated heparin use following digit replantation (Lin et al, 2020). However, it should be underlined that unfractionated heparin was administered subcutaneously in one of the studies included in this meta-analysis (Li et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, low-quality evidence shows that a therapeutic dose of intravenous unfractionated heparin leads to a higher risk of complications when compared with heparin given as an intermittent bolus of unfractionated heparin or subcutaneous heparin, or prostaglandin E1 or no heparin. These results differ from two recent systematic reviews (including one with meta-analysis) that did not find clear evidence of higher complications associated with perioperative thromboprophylaxis in digital replantation (Lin et al, 2020;Reissis et al, 2020).The meta-analysis compared unfractionated heparin use with low-molecular weight heparin and found no clear evidence of higher complications associated with unfractionated heparin use following digit replantation (Lin et al, 2020). However, it should be underlined that unfractionated heparin was administered subcutaneously in one of the studies included in this meta-analysis (Li et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…Twenty-six full-text articles were assessed for eligibility. Twenty of these were excluded (Askari et al, 2006;Buntic & Brooks, 2010;Chen et al, 2021;Couteau et al, 2018;Efanov, 2017;Fukui et al, 1989;Herlihy et al, 2020;Li et al, 2012;Lin et al, 2020;Loisel et al, 2010;Luthringer et al, 2020;Maeda et al, 1991;Noguchi et al, 1999;Noh & Hacquebord, 2020;Pickrell et al, 2020;Reissis et al, 2020;Shaterian et al, 2018;Shi et al, 2013).Other than a prospective trial initiated by some members of our research team (NLM, 2021), the search in EBM reviews did not find other ongoing clinical trials, health technology assessment reports or guidelines. The manual search for relevant gray literature did not allow finding relevant studies either.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral ASA was administered to prevent arterial occlusion. There are several publications on perioperative and postoperative anticoagulant medication ( DeFazio et al., 2016 ; Lee et al., 2016 ; Nishijima et al., 2019 ; Reissis et al., 2020 ; Retrouvey et al., 2019 ; Zhu et al., 2017 ). Nevertheless, the benefits of anticoagulant medication during or after replantation surgery remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, there have been studies reporting the results of replantation of Tamai Zone 2 and more proximal finger amputations, but only a few studies have reported the results of replantation at more distal (Tamai Zone 1) regions [8,9]. In distal-level injuries, the debate about utilizing replantation, local flaps, or other similar repair techniques that require less microsurgical experience is still ongoing [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%